THE ROLE OF CYBER NOTARY IN THE FIELD OF DIGITAL INTERNATIONAL TRADE IN INDONESIA - Ridwan Sidharta; Putu Eka Trisna Dewi (NOTARIIL Jurnal Kenotariatan, 2023)
In Indonesia, a notary refers to a public official appointed by the Government to perform some of the Government’s functions in the field of civil law. In the context of Cyber ​​Notary, the task of a public notary official is more to execute administrative processes combined with security technology by affixing a stamp/seal to a document/agreement file as a form of administration or registration of documents. This research is normative legal research. In this study, the legal materials which had been collected were analyzed in several stages, such as description, systematization and explanation. Philosophical nature of cyber notary in providing legal services to the community is based on the fundamentality of the theory of legal certainty which brings justice and legal certainty to the community into reality, especially through deeds made. The concept of cyber notary is to support Indonesia in the field of international trade based on UNCITRAL. Implementation of the UNCITRAL Model Law on Electronic Commerce in the application of electronic signatures in Indonesia has admittedly been regulated, such as in Article 11 paragraph 1 of the Electronic Information and Transaction Law and Article 59 paragraph 3 of Government Regulation No. 71 of 2019.